2022
DOI: 10.3390/diagnostics12030688
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Accurate, and Robust T2 Mapping of Articular Cartilage by Neural Networks

Abstract: For T2 mapping, the underlying mono-exponential signal decay is traditionally quantified by non-linear Least-Squares Estimation (LSE) curve fitting, which is prone to outliers and computationally expensive. This study aimed to validate a fully connected neural network (NN) to estimate T2 relaxation times and to assess its performance versus LSE fitting methods. To this end, the NN was trained and tested in silico on a synthetic dataset of 75 million signal decays. Its quantification error was comparatively eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Numerous previous studies have demonstrated the potential for deep learning in medical imaging and post-processing [36][37][38]. Among others, Zaiss et al showed the potential for deep learning in qCEST imaging [39].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have demonstrated the potential for deep learning in medical imaging and post-processing [36][37][38]. Among others, Zaiss et al showed the potential for deep learning in qCEST imaging [39].…”
Section: Discussionmentioning
confidence: 99%
“…Equation () describes the signal evolution during a single acquisition. In order to obtain several realizations of the same voxel, the followed model could be exploited 18–20 : gl=ρ1eTR/T1eTEl/T2,l=1,,L where repetition time TR is fixed and several acquisitions are collected varying the echo time TE. Accordingly, g1 corresponds to the first acquisition that adopts TE1 and gL to the last acquisition that adopts TEL.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Equation ( 1) describes the signal evolution during a single acquisition. In order to obtain several realizations of the same voxel, the followed model could be exploited [18][19][20] :…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that NNs can improve robustness to image noise and are more computationally efficient than iterative fitting. One strategy, previously demonstrated for diffusion (31) and T 2 relaxometry (32) problems, is to train a one-dimensionally fully-connected neural network using a large, synthesized training dataset that simulates a forward signal model with random parameter values and Rician noise. These methods improved accuracy and reduced variability compared to the conventional NLLS method.…”
Section: Introductionmentioning
confidence: 99%